Progression of Tibia Fracture Healing Using RUST: Are Early Radiographs Helpful?. Issue 1 (January 2022) - Wojahn, Robert D.; Bechtold, Daniel; Abraamyan, Torgom; Spraggs-Hughes, Amanda; Gardner, Michael J.; Ricci, William M.; McAndrew, Christopher M.
Abstract : Objectives: To report the progression of radiographic healing after intramedullary nailing of tibial shaft fractures using the Radiographic Union Score for Tibial fractures (RUST) and determine the ideal timing of early postoperative radiographs. Design: Retrospective case series. Setting: Urban academic Level 1 trauma center. Patients/Participants: Three hundred three patients with acute tibial shaft fractures underwent intramedullary nailing between 2006 and 2013, met inclusion criteria, and had at least 3 months of radiographic follow-up. Intervention: Baseline demographic, injury, and surgical data were recorded for each patient. Each set of postoperative radiographs were scored using RUST and evaluated for implant failure. Main Outcome Measurements: Postoperative time distribution for each RUST score, RUST score distribution for 4 common follow-up time points, and the presence and timing of implant failure. Results: The fifth percentile and median times, respectively, for reaching "any radiographic healing" (RUST = 5) was 4.0 weeks and 8.4 weeks, "radiographically healed" (RUST = 9) was 12.1 and 20.9 weeks, and "healed and remodeled" (RUST = 12) was 23.5 weeks and 47.7 weeks. At 6 weeks, 84% of radiographs were scored as RUST ≤ 6 (2 or fewer cortices with callus). No implant failure occurred within the first 8 weeks after surgery, and the indication for all 7 reoperations within this period was apparent on physical examination or immediate postoperative radiographs. Conclusions: The median time to radiographic union (RUST = 9) after tibial nailing was approximately 20 weeks, and little radiographic healing occurred within the first 8 weeks after surgery. Routine radiographs in this period may offer little additional information in the absence of clinical concerns such as new trauma, malalignment, or infection. Level of Evidence: Diagnostic Level IV. See Instructions for Authors for a complete description of levels of evidence.